Danofloxacin pharmacokinetics and tissue residues in Bilgorajska geese. (May 2021) - Sartini, Irene; Łebkowska-Wieruszewska, Beata; Lisowski, Andrzej; Poapolathep, Amnart; Giorgi, Mario
Abstract: Danofloxacin is a fluoroquinolone developed for veterinary medicine and used in avian species for the treatment of numerous bacterial infections. However, no pharmacokinetic data have been reported in geese. The aim of the study was three-fold: (i) to evaluate the pharmacokinetics of danofloxacin in geese after single oral (PO) and intravenous (IV) administrations; (ii) to define its residue depletion profile in different goose tissues, and (iii) to recreate a multiple-dose simulation in the practical context of large-scale breeding. Twenty-four healthy geese were randomly divided in three groups each composed of eight animals. Group 1 received danofloxacin IV (5 mg/kg) and groups 2 and 3 were treated PO with the same dose. Blood was collected until 24 h (IV; group 1) and 48 h (PO; group 2) after administration. Two animals from group 3 were sacrificed at 6, 10, 24 and 48 h to collect samples of muscle, heart, kidney, liver, and lung. Danofloxacin was quantified in each matrix using a validated high-performance liquid chromatography method with spectrofluorimetric detection and the pharmacokinetic analysis was performed using non-compartmental and compartmental approaches. Danofloxacin showed a moderate elimination half-life (6.61 h), a slow clearance (0.35 mL/g*h) and a large volume of distribution (1.46 mL/g). The peak plasma concentration after PO administration and the time to reach it were 0.96 μg/mL and 1.70 h, respectively. The oral bioavailability was moderate (58%). Higher residue concentration was found in liver and kidney, compared to the other tissues. If the AUC(0 – 24) value found in the present study is included in the pharmacokinetic/pharmacodynamic index (AUC(0 – 24) /MIC) for the prediction of fluoroquinolones' efficacy, danofloxacin seems to be effective in geese against gram-negative bacteria with a minimum inhibitory concentration (MIC) < 0.076 μg/mL and against S. pneumoniae with a MIC < 0.29 μg/mL after a single PO dose of 5 mg/kg. Liver and kidney showed the highest drug tissue penetration value, with an explorative withdrawal time of 2.6 and 3.8 days, respectively. A practical multiple-dose regimen simulation does not lead to significant plasma drug accumulation. Highlights: Danofloxacin oral bioavailability was moderate (58%). Higher residue concentration was found in liver and kidney, compared to the other tissues. Kidney and liver showed explorative WT of 2.6 and 3.8 days, respectively. The predicted daily therapeutic dose for M. gallisepticum was 9.10 mg/kg.